The relationship between blood glucose levels and meal frequency in stunted children in Medan City - Angwyn, Wilbert; Pratama, Irza Haicha; Fadillah, Qori; Sidabutar, Anjas Domini (Institute of Computer Science (IOCS), 2025)
Stunting remains a major public health concern in Indonesia, affecting millions of children and contributing to long-term growth and metabolic issues. Blood glucose level is the body’s main energy source and is thought to be influenced by meal frequency, particularly in nutritionally vulnerable children. This study aimed to determine whether there is a significant relationship between blood glucose levels and meal frequency in stunted children in Medan City. This research employed an analytical observational design with a cross-sectional approach. A total of 62 stunted children were selected through cluster sampling. Data were collected using glucometer tests for blood glucose and structured questionnaires answered by the parents to assess meal frequency. The Kolmogorov-Smirnov test was applied for normality analysis. The relationship between variables was analyzed using Chi-Square and Mann-Whitney tests. Among the respondents, 56.5% had three meals per day, while 56.5% were found to have hypoglycemia. The Chi-Square test showed a p-value of 0.576 and the Mann-Whitney test yielded a p-value of 0.499. These results indicate no statistically significant relationship between meal frequency and blood glucose levels in stunted children. There is no significant correlation between blood glucose levels and meal frequency among stunted children in Medan City. The variation in blood glucose levels is likely influenced by other factors, such as nutritional status, metabolic adaptation, or environmental conditions. The findings indicate that interventions should emphasize dietary quality over meal frequency, with local health centers like Puskesmas providing personalized nutrition plans and caregiver education to reduce metabolic risks in stunted children.